Cyto-genotoxic evaluation of novel anti-tubercular copper (II) complexes containing isoniazid-based ligands - Fregonezi, Nathália Ferreira; Aparecida de Souza, Fabiana; Aleixo, Nadia Andrade; Stefany da Silva Gomes, Pietra; Silvestre, Rafaela Baldassari; De Grandis, Rone Aparecido [UNESP]; Bento da Silva, Patricia [UNESP]; Pavan, Fernando Rogério [UNESP]; Chorilli, Marlus [UNESP]; Resende, Flavia Aparecida (Elsevier, 2020)
Considering the promising previous results of Cu (II) complexes with isoniazid active ligand against Mycobacterium tuberculosis, the main causative agent of tuberculosis, novel biological assays evaluating its toxicogenic potential were performed to ensure the safe use. The genotoxicity/mutagenicity of the complexes CuCl2(INH)2.H2O (I1), Cu(NCS)2(INH)2.5H2O (I2) and Cu(NCO)2(INH)2.4H2O (I3) was evaluated by the Comet, Micronucleus-cytome and Salmonella microsome (Ames test) assays. The cell viability using resazurin assay indicated that I1, I2 e I3 had moderate to low capacity to reduce the viability of colorectal cells (Caco-2), liver cells (HepG2), lung cells (GM 07492-A and A549) and endothelial cells (HU-VE-C). On genotoxicity/mutagenicity, I1 complex did not induce sizable levels of DNA damage in HepG2 cells (Comet assay), and gene (Ames test) and chromosomal (Micronucleus-cytome assay) mutations. Already, I2 and I3 complexes were considered mutagenic in the highest concentrations used. In light of the above, these results contribute to valuable data on the safe use of Cu(II) complexes. Considering the absence of mutagenicity and cytotoxicity of I1, this complex is a potential candidate for the development of a new drug to the treatment tuberculosis, while I2 and I3 require caution in its use.
Keywords: Ames test; Citotoxicity; Comet assay; Copper(II) complexes; Micronucleus-cytome assay